2018
DOI: 10.1038/s41419-018-0661-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of prohibitin domain family in tumorigenesis and its implication in cancer diagnosis and treatment

Abstract: Prohibitin (PHB) was originally isolated and characterized as an anti-proliferative gene in rat liver. The evolutionarily conserved PHB gene encodes two human protein isoforms with molecular weights of ~33 kDa, PHB1 and PHB2. PHB1 and PHB2 belong to the prohibitin domain family, and both are widely distributed in different cellular compartments such as the mitochondria, nucleus, and cell membrane. Most studies have confirmed differential expression of PHB1 and PHB2 in cancers compared to corresponding normal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 134 publications
6
75
0
1
Order By: Relevance
“…Prohibitin (PHB, also known as PHB1) is a highly conserved and ubiquitously expressed protein localized to different cellular compartments, including the lipid raft of the plasma membrane, mitochondria, cytoplasm or nucleus, and has diverse biological functions [23,24]. In A549 lung cancer cells, an increase in surface PHB expression has been shown to prevent the apoptosis of cancer cells and render them more resistant to paclitaxel [25].…”
Section: Introductionmentioning
confidence: 99%
“…Prohibitin (PHB, also known as PHB1) is a highly conserved and ubiquitously expressed protein localized to different cellular compartments, including the lipid raft of the plasma membrane, mitochondria, cytoplasm or nucleus, and has diverse biological functions [23,24]. In A549 lung cancer cells, an increase in surface PHB expression has been shown to prevent the apoptosis of cancer cells and render them more resistant to paclitaxel [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although PHB has been studied extensively, the subsets of PHB from different subcellular fractions deserve further exploration as their distinct functions and pathological significances remain elusive [27]. In this study, we reported for the first time that the higher expression level of nuclear PHB is significantly associated with breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 83%
“…Loss of p53 and ARF are classical features of glioblastoma (Kim et al, 2012; Mao et al, 2012; Zheng et al, 2008). PHB is required for correct localization of Raf-1 in response to Ras activation and couples EGFR signaling to Ras-Raf-MEK-ERK activation, as well as for mitochondrial functions (Rajalingam and Rudel, 2005; Wei et al, 2017; Yang et al, 2018b). Activation of oxidative and ER stress programs are captured by aberrant activation of proteins such as PRDX4 (Bulleid and Ellgaard, 2011; Zito, 2013).…”
Section: Resultsmentioning
confidence: 99%